The Impact of Legislative Intervention in the Field of Consumer Protection on the Traditional Principles of the Contract - Tradkhoudja, Faissal; Soualem, Sefiane (Journal of Legal Studies and Researches, 2023)
As a result of economic developments, unequal consumption relations emerged in terms of their parties, which prompted modern legislation in the field of consumer protection to intervene in these relations to determine their content because of the failure of the traditional rules of the general theory of the contract in the face of contractual weakness which was reflected in the result on the general principles in the theory of the contract.